THE ROLE OF FOLK MEDICINE IN THE TREATMENT OF DISEASES - Oydinoy Ochilova (Western European Studies, 2025)
This article talks about how traditional medicine has served humanity on the territory of Uzbekistan for centuries, about the methods and medicinal herbs used in medicine. Various diseases are also discussed.
Keywords: traditional medicine; Uzbek khanates